2016
DOI: 10.1007/s00606-016-1323-5
|View full text |Cite
|
Sign up to set email alerts
|

Geographical or ecological divergence between the parapatric species Ephedra sinica and E. intermedia?

Abstract: Understanding the factors that contribute to population genetic structures and ecological niche divergence is crucial for elucidating the biogeographical history and speciation of plants. To disentangle the present phylogeographical patterns and evolutionary history of two closely related parapatric species from Ephedra (Ephedra sinica and E. intermedia), we systematically profiled their population genetic structures, niche divergence and potential speciation processes based on sequence variation of four chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 81 publications
(91 reference statements)
1
8
0
Order By: Relevance
“…Our analysis also revealed that both East-A and East-B lineages located in the eastern region exhibited intraspecific divergence [ Φ ST (East-A versus East-B) = 0.388, p < 0.01], and that the East-A lineage possessed the highest level of genetic diversity ( H T = 0.930, p < 0.05) relative to the other lineages. An analogous phylogeographical genetic structure has been found in other xerophytes, such as R. soongarica , Ephedra sinica , E. intermedia , A. squarrosum , and Panzerina lanata [ 6 , 23 , 28 , 45 , 46 ]. The genetic divergence induced by the Quaternary climate oscillations was the result of this climatic event fostering habitat fragmentation, geographic isolation, and an increase in dispersal distance, which has been well established in many plant species [ 3 , 28 , 29 , 47 ].…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Our analysis also revealed that both East-A and East-B lineages located in the eastern region exhibited intraspecific divergence [ Φ ST (East-A versus East-B) = 0.388, p < 0.01], and that the East-A lineage possessed the highest level of genetic diversity ( H T = 0.930, p < 0.05) relative to the other lineages. An analogous phylogeographical genetic structure has been found in other xerophytes, such as R. soongarica , Ephedra sinica , E. intermedia , A. squarrosum , and Panzerina lanata [ 6 , 23 , 28 , 45 , 46 ]. The genetic divergence induced by the Quaternary climate oscillations was the result of this climatic event fostering habitat fragmentation, geographic isolation, and an increase in dispersal distance, which has been well established in many plant species [ 3 , 28 , 29 , 47 ].…”
Section: Discussionsupporting
confidence: 61%
“…These findings were made based on the fact that the level of genetic diversity among populations was approximately two-fold greater than within populations ( H T = 0.922 vs. H S = 0.470, respectively) ( Table 2 ). The higher differentiation level among populations of N. tangutorum may be due to the intensifying aridification of northwest China induced by geological and paleoclimate scenarios, such as the uplift of the QTP, the fluctuation of glacial–interglacial cycles, as well as the onset and development of EAMS [ 11 , 23 , 46 ]. We hypothesize that the regional vast deserts encompassing the range of N. tangutorum species, such as the Bardain Jaran and Tengger Deserts, could potentially drive population divergence by impeding gene flow between N. tangutorum populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence the genetic divergence between these two species might reflect adaptation to these two environmentally divergent subkingdoms. Genetic divergence between sister species or sister lineages within species due to ecological differentiation have been observed in many plant species in China (Li et al, 2013 ; Wang et al, 2013 ; Sun et al, 2015 ; Yin et al, 2016 ), especially within the “Sino-Himalayan Forest” floristic subkingdom (Fan et al, 2013 ; Liu et al, 2013 ; Zhao et al, 2016 ) where environmental heterogeneity is relatively high.…”
Section: Discussionmentioning
confidence: 99%
“…adaptation of lineages to changes in the environment, Donoghue and Edwards 2014) have been argued to play a role in speciation and lineage diversification (Wiens and Graham, 2005; Cavender-Bares, 2019). Nevertheless, the contribution of ecological factors as primary drivers of speciation remains more elusive (Mayr, 1954; Pyron and Burbrink, 2010; Yin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%